Characteristics of Renal Cell Carcinoma Patients in RSUD Dr Soetomo Surabaya in 2014-2017 - Ferdiansyah Rusdhy; Wahjoe Djatisoesanto; Dyah Erawati; Dyah Fauziah (Health Notions, 2019)
Renal Cell Carcinoma is a type of malignant renal tumour. According to GLOBOCAN 2012 data, it ranked 17th on the most common malignancy in Indonesia with an incidence rate of 1.5 per 100000 citizens. Mortality rates for men is 1.6 per 100000, while it is 0.8 per 100000 case for women. The clinical symptoms of flank pain, flank mass, and hematuria, are usually only found in patients with later stages of cancer development. This descriptive study aims to present data on characteristics of Renal Cell Carcinoma patients. Data were collected from histopathological medical records of RSUD Dr. Soetomo Surabaya. We found that 25 of 40 patients are male, with most patients aged between 50 to 59 at time of diagnosis. Majority of patients worked as a private sector worker, and had high school level education. They presented with stage 2 tumour, with Clear Cell Renal Cell Carcinoma subtype. All 40 patients were treated by Radical Nephroctomy. Keywords: renal cell carcinoma; characteristics